Real-World Treatment Patterns and Survival Outcomes of Patients with Relapsed/Refractory Multiple Myeloma Treated with a Selinexor-Containing Triplet-Based Regimen - Andrew Whiteley; Stephen C. Ijioma; David Ray; Spencer S. Langerman; Ellen Hu; Amy Pierre; Tomer Mark; Habte Yimer (Current Oncology)
Treatment for relapsed/refractory multiple myeloma (RRMM) is complex, with several classes of drugs that can be combined into doublet, triplet, or quadruplet regimens. Real-world studies can help to determine the optimal treatment sequences and dosing through observed usage of drugs outside of clinical trials. Previous clinical trials have demonstrated high rates of durable responses in the treatment of patients with triple-class-exposed RRMM with regimens containing selinexor, a first-in-class, orally available selective exportin 1 inhibitor. This study analyzed real-world treatment patterns and survival outcomes using a nationwide electronic health record-derived, deidentified database of patients with RRMM treated with an eligible selinexor-containing, triplet-based regimen, including combinations with dexamethasone and pomalidomide, bortezomib, carfilzomib, or daratumumab. Patients had a real-world overall survival (rwOS) of 14.7 months (95% CI: 10.6, 20.9) and a derived progression-free survival (dPFS) of 4.7 months (95% CI: 3.4, 6.7). Patients with previous exposure to anti-CD38 monoclonal antibodies (mAbs) in the most recent regimen prior to the selinexor treatment had numerically higher survival outcomes (rwOS, 20.9; dPFS, 8.7 months). These data suggest that, in the real-world setting, the use of selinexor triplet regimens is effective in patients with RRMM, especially those with prior exposure to an anti-CD38 mAb in the immediate prior line of therapy.